ANÁLISIS BIBLIOGRÁFICO DE LOS ESTUDIOS DE VENADOS EN MÉXICO - Mandujano, Salvador (Instituto de Ecología, A.C., 2022)
I analyzed information about studies of white-tailed deer (Odocoileus virginianus), mule deer (O. hemionus), red brocket deer (Mazama americana) and brown brocket deer (M. pandora), in Mexico. I compiled 502 papers written between 1850 and early 2001. Only 24% were accomplished during the first 130 years, and 76% were done in the last 20 years. One percent were books, 13% were specific articles on deer, 12% were sections or chapters in books, 16% were articles on other mammals including deer, 7% were articles in popular science magazines, 11% were thesis and 40% were works published in proceedings of meetings. The brocket deers and mule deer were the least studied species. The white-tailed deer was the most studied species with 75% of the total number of research papers. In particular, only five of the 14 subspecies of white-tailed deer were the most studied: O. v. texanus, O. v. couesi, O. v. sinaloae, O. v. mexicanus and O. v. yucatanensis. Based on this analysis, future research and management should consider: 1) Increase the studies on mule and brocket deers. 2) Carry out studies on genetics and distributions to define how many white-tailed deer subspecies exist in Mexico. 3) Approach studies from a landscape perspective incorporating fragmentation and metapopulations. 4) Carry out long-term studies. 5) Link research to specific management problems. 6) Rescue the ethnozoological knowledge of the indigenous people about deer species. 7) Evaluate the role that deer have as structural agents of vegetation in tropical habitats. 8) Search for ways of management for the white-tailed deer subspecies that inhabit the tropical forest. 9) Classify the country in white-tailed deer management regions or provinces. 10) Create a information data bases. Finally, in this paper a complete list of all bibliography references is presented.